Traces of the Holocaust : journeying in and out of the ghettos - Cole, Tim, 1970- (Continuum, 2011)
The universe began shrinking, ' wrote Elie Wiesel of his Holocaust experiences in Hungary, 'first we were supposed to leave our towns and concentrate in the larger cities. Then the towns shrank to the ghetto, and the ghetto to a house, the house to a room, the room to a cattle car ... ' Adopting an innovative multi-perspectival approach framed around a wide variety of material traces from receipts to maps, name lists to photographs Tim Cole tells stories of journeys into and out of Hungarian ghettos. These stories of the perpetrators who oversaw ghettoization and deportation, the bystanders who w.